Influência das vias de oxidação lipídica e perfil metabólico sobre o desempenho físico de ratos resistentes à obesidade - Cordeiro, Jóctan Pimentel (2021)
Obesity resistance (ROb) is associated with a complex interaction of several metabolic and environmental factors and confers the ability to lower weight gain and body fat deposition even when ingesting high-calorie diets. Thin phenotypes are seen in some individuals and not in others, even with similar dietary patterns and physical activity levels. Even though there are still gaps in the literature on the metabolic processes that explain ROb, there is evidence to support the hypothesis that obese-resistant (OR) animals are more physically active due to their greater capacity to generate energy from lipid oxidation. Animals with better efficiency of lipid oxidation pathways may have less body fat deposition and, consequently, develop greater physical performance. The aim of the present study was to investigate the content of proteins responsible for lipid transport to mitochondria, as well as the main β-oxidation and Krebs cycle regulatory proteins in skeletal muscles in the ROb condition. In addition, to analyze whether OR rats present greater physical performance when submitted to maximal effort tests. Wistar rats (n = 100) with 30 days of age were used, which were submitted to a protocol of induction (3 weeks) and maintenance of obesity (8 weeks), totaling 11 consecutive weeks. The rats were randomized into two groups: a) SD: fed a standard diet (n = 50) and b) HFD: fed a saturated high-fat diet (n = 50). The animals were redistributed into 4 groups using tertiles: Control (C), False-control (FC), Obese-prone (OP) and Obese-resistant (OR). The animals were submitted to maximum physical effort tests (maximum speed on a treadmill exercise coupled to O2 and CO2 analyzer apparatus) to determine the oxygen uptake, carbon dioxide production and respiratory exchange ratio (RER = VCO2/VO2). Specific markers of lipid oxidation were quantified using the Western Blot technique. Body mass, adiposity index (AI), nutritional, biochemical and metabolic profiles were determined. Plasma concentrations of adiponectin, insulin and leptin hormones were evaluated by ELISA. The morphometric characteristics of adipose tissue and skeletal muscle were evaluated post mortem by macroscopic and microscopic studies. The comparison of experimental groups was performed by ANOVA (one and two factors), complemented with Tukey's multiple comparisons test. The significance level considered was 5%. The OP (489 ± 34 g) and FC (467 ± 22 g) groups presented high values of final body mass compared to C (366 ± 34 g) and OR (366 ± 27 g). OR had lower epididymal, retroperitoneal, visceral, sum of fat deposits and AI compared to Ob. OR (26.6 ± 4.63 mg/dL) had values similar to C (23.3 ± 2.98 mg/dL) and higher levels of HDL than FC (22.1 ± 2.16) and OP (21.8 ± 3.12). In the glucose tolerance test, the OR (212 ± 51.9 mg/dL) and C (185 ± 62.8 mg/dL) rats had similar values and both were lower than the OP after 30 minutes (228 ± 35.0) of glycemic overload. OP (1986 ± 199 mg/dL/min) promoted higher values than C (1598 ± 443 mg/dL/min) in glycemic area under curve. Spontaneous physical activity did not differ between groups. However, in the maximum speed physical test, the OR group (17.3 ± 12.3 min) performed better in the duration of the tests than the OP (12.8 ± 9.01 min). The results of maximum O2 uptake (C: 25.5 ± 0.07 mL/kg.min; FC: 32.4 ± 10.1 mL/kg.min; OP: 30.0 ± 15.4 mL/kg.min; OR: 28.4 ± 5.33 mL/kg.min) and RER (C: 0.91 ± 0.19; FC: 0.87 ± 0.34; OP: 0.90 ± 0. 24; OR: 0.71 ± 0.34) showed no significant differences between groups. The OR group had higher protein content of PPARγ compared to C and OP, respectively. In addition, leptin and insulin levels were similar to C. LHS proteins in visceral adipose tissue and UCP-3 in soleus skeletal muscle showed no significant differences between groups. The results of the present study do not show that OR animals have greater lipid oxidative capacity with consequent improvement in physical performance. Contrary to the hypotheses raised here, the findings indicate that OR animals have the ability to resist the development of obesity, however, the evidence is insufficient to affirm that this ability is directly related to greater metabolic and oxidative efficiency.